Leadership Within Islamic Secondary School: A Study Towards Principals’ Challenges - Zunaidi Harun; Muhammad Faizal A. Ghani; Abd. Muhith (JIEMAN: Journal of Islamic Educational Management, 2024)
This study aims at exploring the Malaysian Islamic secondary school principals’ leadership challenges. To respond to the study aim, a qualitative method using some series of interview were applied among seven leaders of Islamic Secondary Schools. The informers were selected based on some criteria such as the length of service as a leader and leadership knowledge. The   data that were analyzed using thematic analysis  reported   seven challenges of Malaysian Islamic secondary school principals’ leadership, namely: (i) lack of knowledge, in particular, the field of school management such as finance, IT, asset,  data  and information,   (ii) lack of management skill to figure out conflicts regarding  incentive differences among senior and novice teachers, (iii) lack of collaboration among stakeholders, (iv) need to allocate more finance for the program of competency development such as enhancing novice teachers’ pedagogical skills, (v) lack of  managing   boarding students with the useful programs, (vi) less concern to support some Ministry of Education’s policies, and (vii) less concern on the changing environment, in particular, the field of pedagogical changes for the post pandemic. The implication of this study is to be aware for the educational stakeholders, in particular, the school principals, to take into account this study findings in order to make self-improvement for enhancing the students learning and school achievement. Penelitian ini bertujuan untuk mengeksplorasi tantangan kepemimpinan kepala sekolah menengah Islam di Malaysia. Untuk menjawab tujuan penelitian, metode kualitatif dengan menggunakan serangkaian wawancara diterapkan pada tujuh pemimpin Sekolah Menengah Islam. Informan dipilih berdasarkan beberapa kriteria seperti lama masa kerja sebagai pemimpin dan pengetahuan kepemimpinan. Data yang dianalisis menggunakan analisis tematik melaporkan tujuh tantangan kepemimpinan kepala sekolah menengah Islam di Malaysia, yaitu: (i) kurangnya pengetahuan, khususnya, bidang manajemen sekolah seperti keuangan, TI, aset, data dan informasi, (ii) kurangnya kemampuan manajemen untuk mengatasi konflik terkait perbedaan insentif antara guru senior dan guru pemula, (iii) kurangnya kolaborasi di antara para pemangku kepentingan, (iv) perlu mengalokasikan lebih banyak dana untuk program pengembangan kompetensi seperti peningkatan keterampilan pedagogis guru pemula, (v) kurang mengelola siswa berasrama dengan program yang bermanfaat, (vi) kurang mendukung kebijakan Kementerian Pendidikan, dan (vii) kurang peduli terhadap perubahan lingkungan, khususnya perubahan pedagogis pascapandemi. Implikasi dari penelitian ini adalah agar para pemangku kepentingan pendidikan, khususnya kepala sekolah, dapat mempertimbangkan temuan penelitian ini untuk melakukan perbaikan diri dalam rangka meningkatkan pembelajaran dan prestasi sekolah.